2022
DOI: 10.1002/rmb2.12438
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent phenotypes of ovarian endometriomas

Abstract: Purpose To analyze the characteristics of the ovarian endometrioma (OE) across the life span of a woman. In the past, the OE has traditionally been viewed as a single, monolithic disease. Today, there are emerging data indicating that OE phenotypes differ according to the age of the woman. Method A narrative review of original articles on OE indexed by PubMed. Results When appearing in infancy and early adolescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 150 publications
(251 reference statements)
0
2
0
Order By: Relevance
“…It is hypothesized that there is a different mechanism in early-onset endometriosis in pre-menarcheal girls [ 33 ]. The presence of eMSCs in NUB has been thought to be the origin of early-onset endometriosis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that there is a different mechanism in early-onset endometriosis in pre-menarcheal girls [ 33 ]. The presence of eMSCs in NUB has been thought to be the origin of early-onset endometriosis [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although pain scores decreased with age, we did not observe an association between age and endometrioma size. Moreover, Benagiano and Guo [ 10 ] reported that the presentation of endometriosis differs with age, suggesting that the pathophysiology of endometriosis may vary with age and may have an impact on pain.…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal endometriosis is less active and less extensive than premenopausal endometriosis [ 158 ]. The disease is likely to present as ovarian endometriomas or deep infiltrating endometriosis, and the pattern of superficial peritoneal endometriosis is rarely seen in this age group [ 161 ].…”
Section: Postmenopausal Endometriosis and The Risk Of Malignant Trans...mentioning
confidence: 99%
“…However, these cells remained morphologically benign with no evidence of atypia or malignant transformation [ 168 ]. There is no doubt that time is an essential factor in cancer development, hence postmenopausal endometriosis has a greater predisposition to malignant transformation [ 161 ].…”
Section: Postmenopausal Endometriosis and The Risk Of Malignant Trans...mentioning
confidence: 99%